Treatment of patients with metastatic urothelial carcinoma and impaired renal function with single-agent docetaxel - Dimopoulos, M.A.; Deliveliotis, C.; Moulopoulos, L.A.; Papadimitriou, C.; Mitropoulos, D.; Anagnostopoulos, A.; Athanassiades, P.; Dimopoulos, C. (Urology, 1998)
Objectives. To evaluate the efficacy and toxicity of single-agent docetaxel in patients with metastatic urothelial carcinoma and impaired renal function. Methods. Eleven consecutive patients previously untreated for metastatic disease with renal impairment (median serum creatinine level of 2.6 mg/dL) were treated with intravenous docetaxel 100 mg/m2 for 1 hour every 21 days. Granulocyte colony-stimulating factor was administered at a dose of 5 μg/kg/day subcutaneously from days 5 to 14. Results. Five of 11 patients achieved a partial response, with time to progression of responding patients ranging from 5 to 22 months or more. The median overall survival rate was 11 months. Renal function improved in 5 of 8 patients with tumor- related renal impairment. Toxicity was primarily hematologic, with 5 patients developing grade 3 or 4 neutropenia; nonhematologic toxicities were manageable. Conclusions. Our preliminary data indicate that single-agent docetaxel therapy may represent an effective therapeutic alternative for patients with advanced urothelial carcinoma and renal insufficiency precluding cisplatin-based combination chemotherapy.